PELAKSANAAN AMAR PUTUSAN GUGATAN REKONVENSI TENTANG HAK-HAK ISTRI DAN ANAK PASCA PERCERAIAN PADA PENGADILAN AGAMA TANJUNG PATI - Asmalinda Asmalinda; Nuzul Rahmayani; Mahlil Adriaman (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2023)
This research includes research with a normative juridical approach. Data sources in this study are primary legal materials, secondary materials, and supporting data. Data collection techniques using literature study techniques. Data processing techniques by editing. Law Number 1 of 1974 contains various provisions regarding marriage and divorce. Data from the first source were immediately analyzed by trying to find a comprehensive explanation of the activities that occurred on the issue of divorce according to the view of Islamic law and after the enactment of Law No. 1 of 1974. The conclusion of this study is: Whether the implementation of Amar Judgment Lawsuit reconvention on the rights of wives and children after divorce in Pengadilan Agama Tanjung Pati can be carried out according to the view of Islamic law and after the enactment of Law No. 1 of 1974. The obstacle to divorce according to the view of Islamic law and after the enactment of Law No. 1 of 1974 is the non-implementation of the results of the judgment after divorce caused by the Defendant not keeping his promise after the divorce.